Um olhar sobre o pró-letramento - Antunes, Janaína Silva Costa (2015)
This work is part of a series of studies produced in the research branch Education and Language in the Post Graduate Program in Education of the Federal University of Espirito Santo. It is aimed at analyzing the literacy policies implemented in the 2000s by the federal government. The search specifically tries to understand the concepts of literacy and “letramento” that supports the Pro-Letramento: Continuing Education Program for Teachers of the early grades of primary education, with emphasis on the analysis of the curriculum and the proposed diagnostic evaluation. It parts of the thesis that, even though literacy and “letramento” have been presented as inseparable processes, the program emphasizes more strongly the aspects of the appropriation of the writing system so, literacy, both in the curriculum and in the diagnostic evaluation. This research takes as theoretical and methodological reference the Bakhtinian assumptions in the field of philosophy of language. The study concludes that the curriculum and the assessment of learning proposed in the program for literacy and early literacy of children, are driven by different concepts of literacy, emphasizing aspects associated with this process.